Fulfilment of Grid Code Obligations by Large Offshore Wind Farms Clusters Connected via HVDC Corridors. (September 2016) - Attya, A.B.; Anaya-Lara, O.; Ledesma, P.; Svendsen, H.G.
Abstract: The foreseen high penetration levels of wind power will force the systems operators to apply restrictive constraints on wind power plants. The ability of offshore wind clusters, which are connected via HVDC, to fulfill the grid codes, especially those related to voltage stability is investigated. This came in the frame of a project to develop an integrated and practical tool to design offshore wind clusters (EERA-DTOC). The applied case studies examine the system stability during and after severe disturbances, and the compliance with the grid codes. Additionally, this paper explains the applied procedure to utilize the outcomes of Net-OP tool, which proposes an optimized topology to connect the wind power clusters to the interconnected power systems. The integrated simulation environment, namely, PSS/E, is used to implement a highly detailed and dynamic model based on the recommendations of Net-OP tool. The results confirm that wind farm clusters respond to faults and disturbances as desired by the grid codes.